Role of Linguistic Devices in Creating Cultural and Historical Specificity in Literary Texts - G. I. Lushnikova; T. Iu. Osadchaia (Научный диалог, 2025)
This article explores the linguistic devices employed in literary texts to construct cultural and historical richness. The materials for analysis are drawn from the novel “The Glass Woman” by a contemporary British author Caroline Lea, which has not previously undergone philological scrutiny, thus underscoring the novelty of this work. The aim of the article is to identify the linguistic means that convey the national and cultural specificity of 17th-century Iceland as presented in this work, as well as to determine their functions and significance in realizing the author’s intent. The analysis focuses on culture specific items, including non-equivalent vocabulary, proper names, lexical items from biblical and pagan texts, proverbs, and landscape vocabulary. The authors argue that studying literary texts as forms of existence and embodiment of a nation’s culture represents one of the current trends in contemporary linguistics. Having employed linguistic, cultural, lexical, semantic, and conceptual methods of text analysis, the authors conclude that linguistic cultural units perform an epistemological function; they facilitate the transmission of a specific national worldview; create representations of the unique identity and value system of Icelanders; promote the establishment of linguistic and cultural connections among communicants (author — characters — reader) and the formation of value universals in the reader’s mind.